Verba Bahasa Bali dalam Ranah Perkebunan Kopi: Analisis Metabahasa Semantik Alami - I Ketut Suar Adnyana (Jurnal Kajian Bali (Journal of Bali Studies), 2020)
This research is a qualitative descriptive study that aimed to determine the semantic structure of Balinese verbs in the realm of coffee plantations with the natural semantics metalanguage theory. The research location was Pucaksari Village, Busungbiu District, Buleleng Regency. The method used to explore data is qualitative. The method used in collecting the data were interview, listening, conversation, and elicitation. The results of the study show that there are eight verbs used in the realm of coffee plantations, include mamula (plant), numbeg (hoe), ngetep (cut), nyambung (connect), ngalap (picking), nyeruh (pound), nyemuh (dry in the sun), and nambunang (collecting). Verb mamula, numbeg, ngetep, nyambung, nyeruh, nyemuh and nambunang having an original meaning ‘do’ that has a polysemy with the original meaning ‘happen’ and it has the exponent X do something to Y, something happened to Y. Verb ngalap andnambunang have the original meaning do has a polysemy with ‘moving’. They have exponent X do something about Y, Y move.